The Effect of Value Congruence on Customer Focus in the Private Life Insurance Sector : A Study of Haryana State in India - Singh, Anoop; Bawa, Pardeep (Prabandhan: Indian Journal of Management, 2018)
It is very important for organizational values to match with employees’ values, which is termed as value congruence. Equally important is customer focus, which is an organizational stance in which all aspects of a company’s production and delivery of goods or services are directed by the best interests of the customers. This study examined the effect of value congruence on customer focus in the private life insurance sector in Haryana. Data were collected on the level of sync organizationalÂ and employees’ values through two different questionnaires from 200 middle and lower level management employees of seven private life insurance companies. The study showed that value congruence was significantly related to customer focus through job satisfaction, employees’ sense of belonging, organizational commitment, and employee loyalty.